Abnormal X chromosome inactivation and sex-specific gene dysregulation after ablation of FBXL10. Issue 1 (December 2016) - Boulard, Mathieu; Edwards, John; Bestor, Timothy
Abstract Background Almost all CpG-rich promoters in the mammalian genome are bound by the multidomain FBXL10 protein (also known as KDM2B, JHDM1B, CXXC2, and NDY1). FBXL10 is expressed as two isoforms: FBXL10-1, a longer form that contains an N-terminal histone demethylase domain with C-terminal F-box, CXXC, PHD, RING, and leucine-rich repeat domains, and FBXL10-2, a shorter form that initiates at an alternative internal exon and which lacks the histone demethylase domain but retains all other annotated domains. Selective deletion ofFbxl10 -1 had been reported to produce a low penetrance and variable phenotype; most of the mutant animals were essentially normal. We constructed mutant mouse strains that were either null forFbxl10 -2 but wild type forFbxl10 -1 or null for bothFbxl10 -1 andFbxl10 -2 . Results Deletion ofFbxl10 -2 (in a manner that does not perturb expression ofFbxl10 -1 ) produced a phenotype very different from theFbxl10 -1 mutant, with craniofacial abnormalities, neural tube defects, and increased lethality, especially in females. Mutants that lacked both FBXL10-1 and FBXL10-2 showed embryonic lethality and even more extreme sexual dimorphism, with more severe gene dysregulation in mutant female embryos. X-linked genes were most severely dysregulated, and there was marked overexpression ofXist in mutant females although genes that encode factors that bind to Xist RNA were globally downregulated in mutant female as compared to male embryos. Conclusions FBXL10 is the first factor shown to be required both for the normal expression and function of theXist gene and for normal expression of proteins that associate with Xist RNA; it is proposed that FBXL10 coordinates the expression of Xist RNA with proteins that associate with this RNA. The function of FBXL10 is largely independent of the histone demethylase activity of the long form of the protein.